Anti-stress-cracking and chemical-resistant ABS (acrylonitrile-butadiene-styrene) composition as well as preparation method and application thereof
By adding ethylene-propylene copolymer and SEBS graft maleic anhydride to ABS resin, the problem of insufficient chemical resistance and stress cracking resistance of ABS composition is solved, and higher chemical resistance in the lead-acid battery industry is achieved Performance and stress crack resistance.
Patent Information
- Application Number
- CN202411536411.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
The chemical resistance and stress crack resistance of existing ABS compositions are poor, especially in the lead-acid battery industry, shell products have high requirements for chemical resistance, and the improvement of existing modification methods is limited.
The chemical resistance and stress cracking resistance of the ABS composition are improved by adding ethylene-propylene copolymer to the ABS resin and using SEBS graft maleic anhydride as a compatibilizer, the specific method includes performing component ratios according to ISO standards Mix and extrude granulation.
It significantly improves the chemical resistance and stress cracking resistance of ABS composition, extends the cracking time under glacial acetic acid solvent, and increases the impact strength, and is suitable for high-demand applications such as lead-acid battery shells.
Smart Images

Figure BDA0005111658060000061 
Figure BDA0005111658060000062 
Figure BDA0005111658060000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of general plastics, and more specifically, relates to an ABS composition resistant to stress cracking and chemicals, and a preparation method and application thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene (ABS) resin is a terpolymer of styrene, acrylonitrile and butadiene. It is widely used in home appliances, automobiles and other related product fields due to its excellent comprehensive performance, dimensional stability, high rigidity and good appearance and light absorption. However, its weather resistance and chemical solvent resistance are poor, which limits its application. In the prior art, high-rubber powder and high-nitrile SAN resin are usually used to modify ABS resin to improve its defects, but it is found that the improvement is limited during the application process. For example, in the lead-acid battery industry, shell products have higher requirements for chemical resistance. Therefore, the art needs to develop an ABS composition that is resistant to stress cracking and chemical resistance. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects or shortcomings of the prior art ABS compositions, such as poor chemical resistance and stress cracking resistance, and to provide a stress cracking and chemical resistant ABS composition.
[0004] Another object of the present invention is to provide a method for preparing the stress cracking resistant and chemical resistant ABS composition.
[0005] Another object of the present invention is to provide applications of the stress cracking resistant and chemical resistant ABS composition.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] A stress cracking and chemical resistant ABS composition, comprising the following components calculated in parts by weight:
[0008] ABS resin 58-92 parts;
[0009] 3-32 parts of ethylene-propylene copolymer;
[0010] Compatibilizer 2-10 parts;
[0011] Wherein, the compatibilizer is SEBS grafted with maleic anhydride.
[0012] In the present invention, ethylene-propylene copolymer is added to ABS resin (acrylonitrile-butadiene-styrene copolymer) to improve its chemical resistance, and SEBS grafted maleic anhydride (SEBS is styrene-ethylene-butylene-styrene block copolymer) is added as a compatibilizer, which has good compatibility with ABS resin, and cooperates with ethylene-propylene copolymer to improve the chemical resistance of the ABS composition, and at the same time has good stress cracking resistance.
[0013] It should be noted that the chemical resistance in the present invention is characterized by stress cracking time.
[0014] Specifically, the tensile strength was determined in accordance with ISO 527-1-2019. The deflection of the test fixture was 2.54 cm. After the specimen was bent to generate internal stress, a solvent was added to the bent part of the specimen. The amount of solvent added was about 0.5 mL. The solvent was glacial acetic acid (about 90 wt%). The specimen corroded by glacial acetic acid was waited to crack, and the cracking time was recorded for characterization.
[0015] It should be noted that, in the stress cracking resistant and chemical resistant ABS composition of the present invention, the content of ABS resin is not less than 55 wt.%.
[0016] It should be noted that the ABS resin in the present invention is 58 to 92 parts, for example but not limited to 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts or 92 parts, and specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific points included in the range.
[0017] The ethylene-propylene copolymer described in the present invention is 3 to 32 parts, for example but not limited to 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts or 32 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the range are no longer exhaustively listed in the present invention.
[0018] The compatibilizer described in the present invention is 2 to 10 parts, for example but not limited to 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the range are no longer exhaustively listed in the present invention.
[0019] Furthermore, the ethylene-propylene copolymer is tested according to ISO 1133-1:2022 method and has a melt flow rate of 1.2 to 50 g / 10 min at 230° C. and 2.16 kg.
[0020] Furthermore, the ethylene-propylene copolymer is tested according to ISO 1133-1:2022 method and has a melt flow rate of 3 to 45 g / 10 min at 230° C. and 2.16 kg.
[0021] The present invention does not specifically limit the melt flow rate of the ABS resin. For example, but not limited to, the melt flow rate of the ABS resin tested according to ISO 1133-1:2022 at 220° C. and 10 kg is 5 to 50 g / 10 min.
[0022] In some specific embodiments, the ABS resin has a melt flow rate of 15 to 40 g / 10 min at 220° C. and 10 kg when tested according to ISO 1133-1:2022.
[0023] Furthermore, the ethylene content in the ethylene-propylene copolymer is 10 to 18 wt%.
[0024] Furthermore, the maleic anhydride grafting rate of the SEBS grafted with maleic anhydride is 0.5wt% to 2.0wt%.
[0025] Furthermore, the maleic anhydride grafting rate of the SEBS grafted with maleic anhydride is 1.2 wt% to 1.5 wt%.
[0026] Specifically, the method for determining the maleic anhydride grafting rate is an acid-base titration method.
[0027] Specifically, (0.1-0.5) g of SEBS grafted maleic anhydride was dissolved in (20-80) mL of xylene, heated under reflux at 80-120° C. for 10-30 min, 2-5 drops of thymol blue indicator were added, and titrated with a KOH-ethanol standard solution with a C1 of about 0.1 mol / L. After the solution turned blue, 0.5-1.5 mL of KOH-ethanol standard solution was continued to be added dropwise, and the total volume V1 of the KOH-ethanol standard solution used was recorded;
[0028] Then titrate with HCl-isopropanol standard solution with C2 of about 0.05 mol / L until the solution turns yellow, and record the volume V2 of HCl-isopropanol standard solution used;
[0029] The grafting rate was calculated using the following formula:
[0030] C MAH%=98.06×[(C1V1-C2V2) / m-C1△V] / 20
[0031] Among them, C MAH is the grafting rate (%); m is the mass of the grafted sample; V1 is the volume of the KOH-ethanol standard solution; C1 is the concentration of the KOH-ethanol standard solution; V2 is the volume of the HCl-isopropanol standard solution; C2 is the concentration of the HCl-isopropanol standard solution; △V is the volume of the KOH-ethanol standard solution consumed in the blank.
[0032] Specifically, the SEBS grafted with maleic anhydride can be commercially available or homemade.
[0033] In a specific embodiment, the SEBS grafted maleic anhydride can be prepared by the following preparation method:
[0034] The method is to extrude a certain amount of SEBS, maleic anhydride, initiator and antioxidant at 160-200°C.
[0035] The maleic anhydride grafting rate was adjusted by adjusting the amount of maleic anhydride added.
[0036] Specifically, the initiator may be diisopropylbenzene hydroperoxide.
[0037] Furthermore, the stress cracking resistant and chemical resistant ABS composition also includes 0.1 to 5 parts of an auxiliary agent.
[0038] Specifically, the auxiliary agent includes one or more of an antioxidant, a lubricant, a weathering agent or a toner.
[0039] Furthermore, the stress cracking resistant and chemical resistant ABS composition comprises the following components calculated in parts by weight:
[0040] ABS resin 75-85 parts;
[0041] 8-20 parts of ethylene-propylene copolymer;
[0042] 3 to 8 parts of compatibilizer.
[0043] In the present invention, commonly used antioxidants may be selected with reference to the prior art, such as but not limited to hindered phenol antioxidants and / or phosphite antioxidants.
[0044] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (Irganox 1098), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 259), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionic acid n-octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylate]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80).
[0045] The phosphite antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite (Irganox 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A.
[0046] In the present invention, commonly used lubricants can be selected with reference to the prior art, such as but not limited to one or more of vinyl bisstearamide, polysiloxane, calcium stearate, magnesium stearate, zinc stearate, PE wax, or PP wax.
[0047] In the present invention, commonly used weathering agents can be selected according to the prior art, such as but not limited to hindered amine light stabilizers and benzotriazole ultraviolet light absorbers.
[0048] Specifically, the hindered amine light stabilizer is at least one of bis-2,2,6,6-tetramethylpiperidinol sebacate, a polymer of N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2,4,6-trichloro-1,3,5-triazine.
[0049] Specifically, the benzotriazole ultraviolet light absorber is one or more of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (UV-P), 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole (UV-234), and 2-(-hydroxy-3-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (UV-236).
[0050] The present invention also provides a method for preparing the above-mentioned stress cracking resistant and chemical resistant ABS composition, comprising the following steps:
[0051] The above components are mixed uniformly according to proportion, and fed into an extruder for extrusion and granulation to obtain an ABS composition that is resistant to stress cracking and chemical resistance.
[0052] Specifically, the extruder is a twin-screw extruder, and the extrusion temperature is 180-220°C.
[0053] In some specific embodiments, the temperature of the twin-screw extruder is as follows: the temperature of zones 1 to 2 is 180-200°C, the temperature of zones 3 to 5 is 190-210°C, and the temperature of zones 6 to 10 is 200-220°C.
[0054] The present invention also protects the use of the above-mentioned stress cracking resistant and chemical resistant ABS composition in the preparation of household appliance structural parts, such as battery housings, embedded copper nut parts and other materials.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The invention provides an ABS composition resistant to stress cracking and chemicals. The chemical resistance and stress crack resistance of the ABS composition can be effectively improved by using ABS resin as a base resin, adding ethylene-propylene copolymer and using SEBS grafted maleic anhydride as a compatibilizer. DETAILED DESCRIPTION
[0057] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0058] The raw materials used in each embodiment and comparative example are:
[0059] ABS resin:
[0060] ABS resin 1: ABS KF-730, tested according to ISO 1133-1:2022 method, the melt flow rate is 23g / 10min at 220℃ and 10kg, purchased from Liaoning Jinfa Technology Co., Ltd.;
[0061] ABS resin 2: ABSDG-MG 94, tested according to ISO 1133-1:2022, with a melt flow rate of 35 g / 10 min at 220 °C and 10 kg, purchased from Tianjin Dagu Chemical Co., Ltd.
[0062] Ethylene-propylene copolymer:
[0063] Ethylene-propylene copolymer 1: Vistamaxx 3000, ethylene content of 11 wt%, tested according to ISO 1133-1:2022 method, melt flow rate of 8 g / 10 min at 230°C and 2.16 kg, purchased from ExxonMobil;
[0064] Ethylene-propylene copolymer 2: Vistamaxx 6102, ethylene content of 16 wt%, tested according to ISO 1133-1:2022 method, melt flow rate of 3 g / 10 min at 230°C and 2.16 kg, purchased from ExxonMobil;
[0065] Ethylene-propylene copolymer 3: Vistamaxx 6502, ethylene content of 13 wt%, tested according to ISO 1133-1:2022 method, melt flow rate of 45 g / 10 min at 230 ° C and 2.16 kg, purchased from ExxonMobil;
[0066] High nitrile SAN: SAN KFA-180, tested according to ISO 1133-1:2022 method, melt flow rate is 10g / 10min at 220℃ and 10kg, purchased from Liaoning Jinfa Technology Co., Ltd.;
[0067] Ethylene-butene copolymer: POE ENGAGE 7447, tested according to ISO 1133-1:2022 method, with a melt flow rate of 5 g / 10 min at 190°C and 2.16 kg, purchased from Dow Chemical;
[0068] Compatibilizer:
[0069] Compatibilizer 1: SEBS-g-MAH, the measured maleic anhydride grafting rate was 1.5wt%, homemade;
[0070] Compatibilizer 2: SEBS-g-MAH, the maleic anhydride grafting rate was 0.8wt%, homemade;
[0071] Compatibilizer 3: SEBS-g-MAH, the maleic anhydride grafting rate was 1.9wt%, homemade;
[0072] Compatibilizer 4: SEBS-g-MAH, the maleic anhydride grafting rate was 1.2wt%, homemade;
[0073] Specifically, a certain amount of SEBS, maleic anhydride, dicumyl peroxide and an antioxidant are mixed and extruded at 180° C. The maleic anhydride grafting rate in SEBS-g-MAH is controlled by adjusting the amount of maleic anhydride added.
[0074] Compatibilizer 5: KRATON TM SEBS-g-MAH FG1901GT, maleic anhydride grafting rate 1.7 wt%, purchased from Kraton;
[0075] Compatibilizer 6: SBS-g-MAH, maleic anhydride grafting rate of 1.5wt%, homemade; the method is the same as SEBS-g-MAH, the only difference is that SBS is used instead of SEBS;
[0076] Additives:
[0077] Weathering agent: a compound of hindered amine light stabilizer and benzotriazole ultraviolet light absorber in a mass ratio of 1:1;
[0078] Antioxidant: a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2;
[0079] Lubricant: vinyl bisstearamide;
[0080] The additives are all commercially available;
[0081] The same raw materials were used in the parallel experiments of the embodiments and comparative examples.
[0082] The ABS compositions described in the examples and comparative examples are prepared according to the formulations in Tables 1 to 2 by the following method, comprising the following steps:
[0083] The above components are mixed evenly according to a proportion, fed into a twin-screw extruder and extruded and granulated to obtain an ABS composition; wherein the extrusion temperature is: the temperature of zones 1 to 2 is 190° C., the temperature of zones 3 to 5 is 200° C., and the temperature of zones 6 to 10 is 210° C.
[0084] Examples 1 to 10
[0085] Table 1 Amount of each component in the stress cracking and chemical resistant ABS composition in Examples 1 to 10 (unit: weight parts)
[0086]
[0087] Comparative Examples 1 to 3
[0088] Table 2 Amount of each component in the ABS composition in Comparative Examples 1 to 3 (unit: weight parts)
[0089]
[0090]
[0091] Performance Testing:
[0092] The properties of the ABS compositions prepared in the above examples and comparative examples were tested, and the specific test items and test methods are as follows:
[0093] 1. Test method:
[0094] (1) Stress cracking resistance test: The tensile strength of the ABS compositions prepared in the examples and comparative examples was measured according to ISO 527-2019. The deflection of the test fixture was 2.54 cm. After bending to generate internal stress, a solvent was dripped into the bent part of the specimen. The amount of the solvent dripped was about 0.5 mL. The solvent was glacial acetic acid (about 90%). The specimen eroded by glacial acetic acid was waited for cracking, and the cracking time was recorded.
[0095] (2) Impact strength test: The impact properties of the ABS compositions prepared in the examples and comparative examples were measured according to ISO 180-2019.
[0096] 2. Test results:
[0097] Table 3 Experimental data of each embodiment and comparative example
[0098]
[0099]
[0100] It can be seen from Table 3 that the stress cracking and chemical resistant ABS compositions prepared in various embodiments of the present invention have good stress cracking and chemical resistance properties. Specifically, the stress cracking time is more than 55s, and the impact strength is not less than 15kJ / m 2 .
[0101] It can be seen from Comparative Example 1 that the comprehensive performance of the ABS composition obtained by using other substances instead of the ethylene-propylene copolymer is significantly reduced.
[0102] It can be seen from Comparative Example 2 that the stress cracking resistance and chemical resistance of the ABS composition prepared by using the traditional high-nitrile SAN resin are significantly lower than those in the example.
[0103] It can be seen from Comparative Example 3 that if other substances are used to replace the compatibilizer of the present invention, the performance of the prepared ABS composition is significantly worse than that of the example.
[0104] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A stress cracking and chemical resistant ABS composition, characterized in that: The composition comprises the following components calculated by weight: ABS resin 58-92 parts; 3-32 parts of ethylene-propylene copolymer; Compatibilizer 2-10 parts; Wherein, the compatibilizer is SEBS grafted with maleic anhydride.
2. The stress cracking resistant and chemical resistant ABS composition according to claim 1, characterized in that: The ethylene-propylene copolymer is tested according to ISO 1133-1:2022 and has a melt flow rate of 1.2 to 50 g / 10 min at 230° C. and 2.16 kg.
3. The stress cracking resistant and chemical resistant ABS composition according to claim 1, characterized in that: The ethylene content in the ethylene-propylene copolymer is 10 to 18 wt%.
4. The stress cracking resistant and chemical resistant ABS composition according to claim 1, characterized in that: The maleic anhydride grafting rate of the SEBS grafted with maleic anhydride is 0.5 wt % to 2.0 wt %.
5. The stress cracking resistant and chemical resistant ABS composition according to claim 4, characterized in that: The maleic anhydride grafting rate of the SEBS grafted with maleic anhydride is 1.2 wt % to 1.5 wt %.
6. The stress cracking resistant and chemical resistant ABS composition according to claim 1, characterized in that: The ABS resin is tested according to ISO 1133-1:2022 method and has a melt flow rate of 5 to 50 g / 10 min at 220° C. and 10 kg.
7. The stress cracking resistant and chemical resistant ABS composition according to claim 1, characterized in that: It also includes 0.1 to 5 parts of auxiliary agents.
8. The stress cracking resistant and chemical resistant ABS composition according to claim 7, characterized in that: The auxiliary agent includes one or more of an antioxidant, a lubricant, a weathering agent or a toner.
9. A method for preparing the stress cracking resistant and chemical resistant ABS composition according to any one of claims 1 to 8, characterized in that: The steps include: The above components are mixed uniformly according to proportion, and fed into an extruder for extrusion and granulation to obtain an ABS composition that is resistant to stress cracking and chemical resistance.
10. Use of the stress cracking resistant and chemical resistant ABS composition according to any one of claims 1 to 8 in the preparation of household appliance structural parts.